The Urey Instrument: An Advanced In Situ Organic and Oxidant Detector for Mars Exploration - Aubrey,AD; Chalmers,JH; Bada,JL; Grunthaner,FJ; Amashukeli,X; Willis,P; Skelley,AM; Mathies,RA; Quinn,RC; Zent,AP; Ehrenfreund,P; Amundson,R; et al. (Astrobiology, 2008)
The Urey organic and oxidant detector consists of a suite of instruments designed to search for several classes of organic molecules in the martian regolith and ascertain whether these compounds were produced by biotic or abiotic processes using chirality measurements. These experiments will also determine the chemical stability of organic molecules within the host regolith based on the presence and chemical reactivity of surface and atmospheric oxidants. Urey has been selected for the Pasteur payload on the European Space Agency's (ESA's) upcoming 2013 ExoMars rover mission. The diverse and effective capabilities of Urey make it an integral part of the payload and will help to achieve a large portion of the mission's primary scientific objective: “to search for signs of past and present life on Mars.” This instrument is named in honor of Harold Urey for his seminal contributions to the fields of cosmochemistry and the origin of life.